Managing time & stress - Marshall, Jared; Sheahan, Peter; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2003)
In this punchy, amusing and informative program, Peter Sheahan offers advice on how students can best plan their time on a week-by-week basis. He also provides a clear insight on not just coping, but excelling during busy and potentially stressfull exam periods
Title from title screen
Executive producer, Mark McAuliffe ; editor, Jared Marshall ; camera, Leigh Tilson, Matthew Lovering
[Presenter]: Peter Sheahan
Keywords: Time management; Stress management; Students